Peranan Kolektor Keliling terhadap Kepuasan dan Loyalitas Nasabah di Lembaga Perkreditan Desa Pakraman Renon - DISNUYANA, WAYAN; SUDARMA, I MADE; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Role of Collectors in Increasing Customer Satisfaction and Loyalty  in Pakraman Village Credit Institution, Renon Pakraman Renon Village Credit Institution (LPD) was only able to attract as many as 21.7% clients until September 2018. In addition, there is increasing competition between financial institutions in the village. Therefore, LPD Pakraman Renon is trying to be more proactive in managing its market and optimizing its service system, one of which is by attracting customer interest. This study aims to determine the role of mobile collectors in customer satisfaction and loyalty toward LPD Pakraman Renon. The number of samples in this study were 80 respondents. Data collection was carried out by interviewing, distributing questionnaires, and through literature study. This research uses descriptive analysis techniques and SEM-PLS analysis. The results show that (1) collector service quality has a significant effect on customer satisfaction at LPD Pakraman Renon, (2) satisfaction has a significant effect on customer loyalty at LPD Pakraman Renon, (3) collector service quality has no effect on customer loyalty at LPD Pakraman Renon, (4) collector service quality has a significant effect on customer loyalty through satisfaction as a mediation at LPD Pakraman Renon. The management of LPD Pakraman Renon should improve the quality of collector services in order to improve customer satisfaction.